The Mental Health Toll of the COVID-19 Pandemic on Older Adults with Migraine: A Prospective Analysis of Depression Using the Canadian Longitudinal Study on Aging - MacNeil A; Taunque A; Leo SN; Li G; de Groh M; Jiang Y; Fuller-Thomson E (Journal of Pain Research)
Andie MacNeil,1,2 Aneisha Taunque,2 Sarah N Leo,1 Grace Li,3 Margaret de Groh,4 Ying Jiang,4 Esme Fuller-Thomson1,2 1Factor-Inwentash Faculty of Social Work, University of Toronto, Toronto, Ontario, Canada; 2Institute for Life Course and Aging, University of Toronto, Toronto, Ontario, Canada; 3Department of Sociology, University of Victoria, Victoria, British Columbia, Canada; 4Applied Research Division, Center for Surveillance and Applied Research, Public Health Agency of Canada, Ottawa, Ontario, CanadaCorrespondence: Esme Fuller-Thomson, Institute for Life Course & Aging, Factor-Inwentash Faculty of Social Work Cross-Appointed to Faculties of Medicine & Nursing, University of Toronto, 246 Bloor St. West, Toronto, ON, M5S 1V4, Canada, Tel +1 (416) 978-3269, Fax +1 (416) 978-7072, Email esme.fuller.Thomson@utoronto.caBackground: Individuals with migraine are recognized to have a heightened risk of depression compared to the general population. The COVID-19 pandemic and associated public health restrictions exacerbated several known risk factors for depression, but limited longitudinal research has examined the impact of the pandemic on the mental health of people with migraine.Aim: To examine the cumulative incidence of depression and recurrent depression among older adults with migraine, and to identify factors associated with depression among older adults with migraine during the pandemic.Methods: Data came from four waves of the Canadian Longitudinal Study on Aging’s comprehensive cohort (n=2181 with migraine). The outcome of interest was a positive screen for depression based on the CES-D-10 during the autumn of 2020. Bivariate and multivariate logistic regression analyses were conducted.Results: Older adults with migraine, both with and without a history of depression, experienced increases in depression when compared to pre-pandemic levels, and when compared to older adults without migraine. The risk of incident and recurrent depression was higher among those who felt lonely and those who experienced an increase in family conflict during the pandemic. The risk of incident depression only was higher among those who experienced difficulty accessing healthcare and those who experienced other family challenges, such as increased caregiving responsibilities. The risk of recurrent depression only was higher among those who felt left out socially, those with functional limitations, and those whose income did not satisfy their basic needs.Conclusion: Targeted interventions are needed to support the mental health of older adults with migraine.Keywords: migraine, depression, COVID-19, older adults, CLSA